Sudden cardiac deaths: Role of nonischemic myocardial disorders-Part 1 - Pradeep Vaideeswar; Shashank Tyagi; Saranya Singaravel; Supreet P Marathe (Wolters Kluwer Medknow Publications, 2021)
Sudden death, a catastrophic event, falls within the purview of the forensic experts. It is often caused by cardiovascular diseases, which may be evident or occult. A vast majority of sudden cardiac deaths (to the extent of 90%) are due to ischemia of the working or conducting myocardial tissues consequent to coronary artery diseases. A heterogeneous group of nonischemic myocardial disorders, most producing structural abnormalities are responsible for the remainder; they predominantly represent various cardiomyopathies. This review, in two parts, covers sudden cardiac death in medicolegal autopsies with an approach to some common and uncommon nonischemic myocardial diseases that have a genetic and/or nongenetic basis.